Setting priority list for construction works of bicycle path segments based on Eckenrode rating and ARAS-F decision support method integrated in GIS - Zagorskas, Jurgis; Turskis, Zenonas (Transport, 2020)
Bicycling and walking are essential elements of sustainable transportation. These transportation modes effectively reduce the negative environmental impacts of transport and improve the quality of life. It is not only recognized by governments but also naturally become more prevalent in modern society. Nowadays research on bicycling and interest in related topics is dramatically increasing, but while researchers focus on modern technologies and collecting data from portable devices, there are quite a few studies on the effectiveness of investments in bicycle infrastructure, and even less discussed is a question how to set the priorities for construction works of the bicycle path network. To fill this gap this paper presents the universal method of ranking the priorities for development and renewal of bicycle pathway segments. The process is realized by hybrid Multi-Criteria Decision-Making (MCDM) Additive Ratio ASsessment with Fuzzy (ARAS-F) model, based on Eckenrode rating. Given criteria and their weights apply only to the specifics of this case study, and it need adaptation if used for other territories. Presented case study gives insight into the task of upgrading bicycle networks – how to overcome the inequalities, fragmentation and build missing links. Developed hybrid MCDM model integrated into Geographic Information System (GIS) allows quickly find rationally balanced solutions and develop bicycle network in efficient way.